Determinants of Household’s Healthcare Payment in Nepal: Evidence from Living Standard Survey III Data - Thapa, Arjun Kumar; Singla, Sonia (Journal of Advanced Academic Research, 2019)
Healthcare financing has always remained an important development issue for Government of Nepal to ensure equity and availability of basic health care services for all but the largest portion of health financing is met by out of pocket payment (OOP), a private financing source of households. So this study aims to assess the situation of private healthcare financing and analyze the factors associated with it. A cross sectional descriptive cum analytical study was designed based on living standard survey data of CBS (2012), Nepal. It is a rich and country wide representative data comprising 5988 households. The study applied logistic regression to analyze the determinants of out of pocket payment. The major findings of the study shows a particular household’s mean healthcare cost was NRs. 1119 for acute illness and cost of medicine occupied the major portion of the cost. The mean OOP healthcare cost is higher for urban residents, mountain dwellers, and households belonging to province 3 and people belonging to highest wealth quintiles. The odds of household facing OOP payment increases for male headed households, larger households and households belonging to province number 2. Conversely, odds of household facing OOP decreases for households residing in urban and province number4.  The study concludes that out of pocket payment is an important source of private healthcare financing source. So there is a need to effectively implement the demand side financing programs and health insurance scheme to protect households from financial burden.